2016
DOI: 10.1007/s10508-015-0681-3
|View full text |Cite
|
Sign up to set email alerts
|

Pupillary Response as an Age-Specific Measure of Sexual Interest

Abstract: In the visual processing of sexual content, pupil dilation is an indicator of arousal that has been linked to observers’ sexual orientation. This study investigated whether this measure can be extended to determine age-specific sexual interest. In two experiments, the pupillary responses of heterosexual adults to images of males and females of different ages were related to self-reported sexual interest, sexual appeal to the stimuli, and a child molestation proclivity scale. In both experiments, the pupils of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 73 publications
6
49
0
Order By: Relevance
“…A recent study therefore reexamined whether pupillary response can provide an age-specific measure of sexual interest using highly sensitive, contemporary eye-tracking equipment (Attard-Johnson, Bindemann, & Ó Ciardha, 2016). Consistent with previous research, heterosexual male observers displayed larger pupils during the viewing of adult women (Hess et al, 1965;Rieger et al, 2015;Rieger & Savin-Williams, 2012).…”
supporting
confidence: 55%
See 2 more Smart Citations
“…A recent study therefore reexamined whether pupillary response can provide an age-specific measure of sexual interest using highly sensitive, contemporary eye-tracking equipment (Attard-Johnson, Bindemann, & Ó Ciardha, 2016). Consistent with previous research, heterosexual male observers displayed larger pupils during the viewing of adult women (Hess et al, 1965;Rieger et al, 2015;Rieger & Savin-Williams, 2012).…”
supporting
confidence: 55%
“…However, the study by Attard-Johnson et al (2016) was also limited in some important respects. One caveat is that the pupils of heterosexual female observers also revealed dilation during the viewing of adult women.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, in the incongruent condition, instructed antisaccades away from sexually relevant information should be in conflict with exogenous generation processes towards significant information. Although previous studies point to sexual nonspecificity in sexual information processing in women that occurs independent from assessment methods (e.g., Attard-Johnson et al, 2016;Chivers, Rieger, Latty, & Bailey, 2004;Dawson & Chivers, 2016;Lippa, 2006), we included male and female participants. However, it is an empirical question whether men and women show sexual-interest specific differences in the performance of pro-and antisaccades in the CPAP.…”
Section: The Present Studymentioning
confidence: 99%
“…While participants predominately looked at the face of stimuli rated in the loveeliciting condition, they fixated comparatively more often body parts of stimuli in the lusteliciting condition. In addition, other eye tracking studies revealed that eye movement data, for example on pupil dilation or gaze time, differed between sexually relevant and irrelevant stimulus material (e.g., Attard-Johnson, Bindemann, & Ciardha, 2016;Bradley, Costa, & Lang, 2015;Dawson & Chivers, 2016;Fromberger et al, 2012;. Dawson and Chivers (2016) suggested that these findings imply sexual interest-specific allocation of attention that influences 4 sexual information processing as well as behavioral reactions both at an automatic and an intentional level.…”
mentioning
confidence: 98%